A simulation algorithm for a single server retrial queuing system with batch arrivals - Florea Ion; Nǎnǎu Corina-Ştefania (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2015)
Many systems of real word are modeled by retrial queuing system with batch arrivals. Analytical formulas for this class of systems are complicated and address only particular cases. The paper presents a study approach for this kind of systems, based on discrete event simulation. It is shown that the given algorithm has a polynomial complexity. Also, the object-oriented design we used for implementation is sketched.